What Do Religion Scholars Really Want? Scholarly Values in the Scientific Study of Religion. Issue 1 (29th January 2020) - Shults, F. LeRon; Wildman, Wesley J.; Taves, Ann; Paloutzian, Raymond F.
Abstract: This article presents selected findings of the Values in Scholarship on Religion (VISOR) project. Conversations about the values and norms that ought to shape the academic study of religion are quite common but typically based on anecdotal evidence and personal experience. The goal of VISOR was to gather data that could ground debates about the values that scholars of religion prize. Here, we present statistical analyses of VISOR data that shed light on the values guiding members of the Society for the Scientific Study of Religion (SSSR) and the ways in which these compare with the values of members of other academic associations and other disciplines that study religion. Compared to current members of SSSR, members of the broader field of scholars whose approach to religion is sociological are more likely to be younger, female, liberal, and nonreligious. This sea change will put pressure on the SSSR to adapt.